Search for dark sectors: beyond the standard model of particle physics - Jesus, Álvaro Santos de (2024)
The Standard Model of Particle Physics is one of the best theoretical models in the history of physics. However, there is a growing number of pieces of evidence pointing to the fact that the model is, in fact, incomplete. In this work, we discuss the existence and properties of extensions to the Standard Model called Dark Sectors, presenting methods of detection for these new particles and possible candidates, such as WIMP dark matter, Axion-Like Particles, and the Dark Photon. Firstly, we use a famous extension to the Standard Model known as the Two Higgs Doublet Model augmented by a new U(1)Lµ−Lτ gauge symmetry to propose a solution to the muon anomalous magnetic moment tension while presenting a viable dark matter candidate simultaneously. Then, we propose an experiment for searching dark sector particles in Brazil by repurposing some subsystems of the currently inactive UVX synchrotron light generator, named “Search for Dark Sectors” (SeDS). Within the framework of SeDS, we find that, if constructed, this experiment has the potential to produce appealing results in the search for dark photons and Axion-Like Particles, being able to search for regions on the parameter space {mA′, ϵ2} for dark photons and {gaee, ma} for the Axion-Like particles that are currently unexplored by other experiments in the literature, thus being a promising experiment in the search for dark sectors.